2016
DOI: 10.4209/aaqr.2015.07.0438
|View full text |Cite
|
Sign up to set email alerts
|

Passive Release of Fungal Spores from Synthetic Solid Waste Surfaces

Abstract: Passive release of fungal spores can occur from various natural and anthropogenic sources leading to significant concentrations in ambient air with potential effect on health and climate. The estimation of fungal spore release is a critical parameter necessary for the realistic assessment of health risk using dispersion models and in global climate modeling. This paper presents results from experiments conducted to seek a better understanding of the process of passive fungal spore due to wind. Laboratory studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…cladosporioides ) with the two dry air spora, however the correlation values obtained were relatively lower compared to the wind speed. This reveals that high wind speed >8 ms −1 may inhibit the fungal spore release from conidia 40 , 42 . A .…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…cladosporioides ) with the two dry air spora, however the correlation values obtained were relatively lower compared to the wind speed. This reveals that high wind speed >8 ms −1 may inhibit the fungal spore release from conidia 40 , 42 . A .…”
Section: Resultsmentioning
confidence: 91%
“…The ascus is said to rupture when the water content inside it increases by water absorption from the atmospheric moisture (humidity) and when the water content decreases due to the evaporation from the ascus (at high atmospheric temperature) 41 . On the other hand, when the spores get dislodged from the conidiophore due to the external disturbances caused by air currents or by insect landing on the fungi, then such a release mechanism is termed as a ‘passive’ release 39 , 42 . Thus, higher temperature (>30 °C) and lower relative humidity (<70%) are primarily responsible for the active release 34 , 43 whereas higher wind speed plays an important role in passive release of the spores 34 , 44 .…”
Section: Resultsmentioning
confidence: 99%
“…The spore release rate from colonies was found to increase with the blowing air speed. Previous studies found that gusty airflow with high turbulence intensity could enhance spore aerosolization (Gopalakrishnan et al, 2016).…”
Section: Introductionmentioning
confidence: 97%
“…When a fungal colony develops on a moldy surface, fungal propagules may be released from the surface into the indoor air (Gopalakrishnan et al, 2016). Fungal spores can easily be detached from the colonies by disturbance and then dispersed into the air (Frankel et al, 2014;Piekarska et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…After a period of vegetative growth, the foot cells grow into air and form aerial hyphae. The aerial hyphae can differentiate into conidiophores, which give rise to a large number of spores (Wang et al, 2020;Gopalakrishnan et al, 2016). Previous studies have showed that significant amounts of visible molds were found in ceiling tiles and wallpapers (Nielsen, 2003).…”
Section: Introductionmentioning
confidence: 99%